Accessing Indigenous Long-Term Care - Gionnas, Danielle; Bianchi, Andria; Benoit, Leonard; Rodrigues, Kevin (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2021)
The purpose of this commentary is to present and respond to the gap that currently exists in providing culturally inclusive residential long-term care options for Indigenous peoples in Ontario. After presenting statistics regarding the Indigenous population and long-term care options, we argue that we have an ethical responsibility to offer more culturally inclusive long-term care.